IMPLEMENTASI PRINSIP GOOD GOVERNANCE TERHADAP EFEKTIFITAS PELAYANAN PUBLIK DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL - Supratman Tahir (DEMOKRASI, 2022)
This study aims to determine the implementation of the principles of good governance on the effectiveness of public services at the Department of Population and Civil Registration of Bone Regency. This research was conducted using a qualitative approach with a descriptive (type) format. Data collection techniques used in this study include: observation, interviews, documentation. The data analysis techniques used are: data reduction, data presentation and conclusion drawing. The results of this study state that: (1) Implementation of Good Governance Principles on the Effectiveness of Public Services at the Population and Civil Registration Office of Bone Regency has not been fully effective, directed and systematic, in providing public services to the community in accordance with the expectations and needs of the community. Judging from the characteristics of the principles of good governance that have been applied as follows: accountability, transparency, participation and the rule of law. And one of them has not been running effectively, namely the principle of accountability while the principles of transparency, participation, and the rule of law have been quite effective in accordance with the expectations and needs of the community. (2) The factors that influence the implementation of the principles of good governance on the effectiveness of public services at the Department of Population and Civil Registration of Bone Regency can be seen from the availability of adequate facilities and infrastructure. Keywords: Good Governance, Effectiveness, Public Service